2020
DOI: 10.1111/jth.14715
|View full text |Cite
|
Sign up to set email alerts
|

Patients with aortic stenosis have von Willebrand factor abnormalities and increased proliferation of endothelial colony forming cells

Abstract: Background Patients with aortic stenosis (AS) can experience bleeding complications including gastrointestinal bleeding from angiodysplastic lesions due to acquired von Willebrand syndrome. Studies have pointed to a role for von Willebrand factor (VWF) in angiogenesis. Objective The objective of this study was to assess VWF defects in AS patients over time and the impact on angiogenesis using patient‐derived endothelial colony‐forming cells (ECFCs). Patients/Methods Plasma sample collection and ECFC isolations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[13] Consequently, this leads to the loss of VWF high-molecular-weight multimers and platelet-mediated hemorrhage. [14,15] This type of acquired von Willebrand disease (aVWD) ascribed to high shear rate is known to occur in patients with AVS, hypertrophic cardiomyopathy, and mitral and aortic insufficiency. [16]…”
Section: All Data Generated or Analyzed During This Study Are Include...mentioning
confidence: 99%
“…[13] Consequently, this leads to the loss of VWF high-molecular-weight multimers and platelet-mediated hemorrhage. [14,15] This type of acquired von Willebrand disease (aVWD) ascribed to high shear rate is known to occur in patients with AVS, hypertrophic cardiomyopathy, and mitral and aortic insufficiency. [16]…”
Section: All Data Generated or Analyzed During This Study Are Include...mentioning
confidence: 99%
“…Previously, members of the miR-17-92 cluster, to which miR-19 belongs, were reported to regulate myocardial fibrosis and angiogenesis [34]. However, the role of angiogenesis is still unclear, with some studies reporting that the degree of myocardial angiogenesis is accompanied by increased hypertrophy, worsening of systolic function, and severe AS [35,36]. On the other hand, a study demonstrated that increased angiogenesis and cardiomyocytes proliferation prevent maladaptive remodeling in a model of LV pressure-overload [37].…”
Section: Aortic Valve Stenosismentioning
confidence: 99%
“…Previous studies have shown that endothelial von Willebrand factor (VWF) is a negative regulator of angiogenesis 18 . Patient derived endothelial colony‐forming cells from both patients with type 3 VWD and patients with aortic stenosis (AVWS) display abnormal angiogenesis in vitro 19,20 . In vivo studies in VWF knockout mice show increased vessel growth in the ears and increased tubule formation in Matrigel plugs at 7 days when compared with wild type.…”
Section: Von Willebrand Factor In Angiogenesis and Angiodysplasia In mentioning
confidence: 99%